2014
DOI: 10.1002/ijc.28942
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-positive diffuse large B-cell lymphoma association is not only restricted to elderly patients

Abstract: Diffuse large B-cell lymphoma (DLBCL), the most common group of malignant lymphomas, account for 30% of adult nonHodgkin lymphomas. The 2008 World Health Organization (WHO) classification included a new entity, Epstein-Barr virus (EBV)1 DLBCL of the elderly, affecting patients aged 50 years or older. However, some reports of younger EBV1 DLBCL cases, without evidence of underlying immunosuppression, can be found. The role of EBV in tumor microenvironment composition in DLBCL is still not well understood. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 45 publications
8
45
0
Order By: Relevance
“…The predominance of males in our series (male to female ratio of 3.6) is similar to what has been observed in the elderly. 4,5,9,24 However, all patients had nodal disease, with only 11% showing extranodal involvement as well. This is in contrast with the higher incidence of extranodal disease reported in the elderly population.…”
Section: Clinical Features and Coursementioning
confidence: 99%
See 3 more Smart Citations
“…The predominance of males in our series (male to female ratio of 3.6) is similar to what has been observed in the elderly. 4,5,9,24 However, all patients had nodal disease, with only 11% showing extranodal involvement as well. This is in contrast with the higher incidence of extranodal disease reported in the elderly population.…”
Section: Clinical Features and Coursementioning
confidence: 99%
“…8 Our results are similar to those reported recently by Hong et al 25 and contrast with the poor prognosis observed by Beltran et al and Cohen et al in a limited number of patients. 22,24 Seventy-nine percent of patients received rituximab in addition to chemotherapy, likely contributing to the good outcome. It has been shown that rituximab chemotherapy improved survival of patients with THRLBCL 32 and EBV 1 DLBCL-E 7,21 and abolished the negative impact of EBV on the outcome of patients with DLBCL 16 and DLBCL-E.…”
Section: Clinical Features and Coursementioning
confidence: 99%
See 2 more Smart Citations
“…EBV-positive DLBCL is defined as an EBV-positive monoclonal large B cell lymphoproliferation occurring in an immunocompetent patient greater than 50 years of age with no history of prior lymphoma. The age cutoff emphasizes the tendency of these tumors to arise in individuals of advanced age (Balague Ponz et al 2008;Cho et al 2008;Cohen et al 2014), though EBV-positive DLBCL has been reported in younger immunocompetent patients, albeit rarely (Cohen et al 2014;Ao et al 2014;Beltran et al 2011a). It is presently unclear whether elderly patients can be truly considered immune competent, and thus distinct from other EBV-positive DLBCL subtypes, or whether the EBV reactivation in these patients is due to age-related T cell dysfunction (Miller 1996).…”
Section: Ebv-positive Dlbcl As a Disease Modelmentioning
confidence: 99%